Perinatal asphyxia: CNS development and deficits with delayed onset - Herrera-Marschitz, Mario; Neira-Pena, Tanya; Rojas-Mancilla, Edgardo; Espina-Marchant, Pablo; Esmar, Daniela; Perez, Ronald; Munoz, Valentina; Gutierrez-Hernandez, Manuel; Rivera, Benjamin; Simola, Nicola; Bustamante, Diego; Morales, Paola; et al. (Frontiers in Neuroscience, 2014)
Perinatal asphyxia constitutes a prototype of obstetric complications occurring when pulmonary oxygenation is delayed or interrupted. The primary insult relates to the duration of the period lacking oxygenation, leading to death if not re-established. Re-oxygenation leads to a secondary insult, related to a cascade of biochemical events required for restoring proper function. Perinatal asphyxia interferes with neonatal development, resulting in long-term deficits associated to mental and neurological diseases with delayed clinical onset, by mechanisms not yet clarified. In the experimental scenario, the effects observed long after perinatal asphyxia have been explained by over expression of sentinel proteins, such as poly(ADP-ribose) polymerase-1 (PARP-1), competing for NAD+ during re-oxygenation, leading to the idea that sentinel protein inhibition constitutes a suitable therapeutic strategy. Asphyxia induces transcriptional activation of pro-inflammatory factors, in tandem with PARP-1 overactivation, and pharmacologically induced PARP-1 inhibition also down-regulates the expression of proinflammatory cytokines. Nicotinamide has been proposed as a suitable PARP-1 inhibitor. Its effect has been studied in an experimental model of global hypoxia in rats. In that model, the insult is induced by immersing rat foetuses into a water bath for various periods of time. Following asphyxia, the pups are delivered, treated, and nursed by surrogate dams, pending further experiments. Nicotinamide rapidly distributes into the brain following systemic administration, reaching steady state concentrations sufficient to inhibit PARP-1 activity for several hours, preventing several of the long-term consequences of perinatal asphyxia, supporting the idea that it constitutes a lead for exploring compounds with similar or better pharmacological profiles.